Feasibility of Live-Performed Music Therapy for Extremely and Very Preterm Infants in a Tertiary NICU - van Dokkum, Nienke H.; Jaschke, Artur C.; Ravensbergen, Anne-Greet; Reijneveld, Sijmen A.; Hakvoort, Laurien; de Kroon, Marlou L. A.; Bos, Arend F. (Frontiers in Pediatrics, 2020)
Objective: We aimed to investigate the feasibility of live-performed music therapy for extremely and very preterm infants admitted to the neonatal intensive care unit (NICU), and their parents, starting the first to second week after birth. They may benefit from live-performed music therapy as comforting non-pharmacological intervention. Study design: We included infants born before 30 weeks’ gestation in a single center NICU study. Live-performed music therapy was provided three times per week, tailored to the infant’s medical condition. Parents were actively involved. Feasibility was determined as a combination of participation, drop-out, overstimulation (based on COMFORT-Neo scores), and evaluations of the intervention by parents and nurses (using a questionnaire on perceived effects on the parent, their infant and the NICU sound environment). Results: We included 18 infants (90% participation rate), with a gestational age of median 27 weeks (IQR 26-28 weeks), 61% males. One infant (5.6%) dropped-out. Differences of COMFORT-Neo scores during and after sessions compared with before sessions were non-significant; overstimulation by music therapy did not occur. Parents reported high satisfaction (highest score possible of 7) with the interventions and reported improvements in both infant and their own respiratory rates. Nurses also reported high satisfaction with the intervention and perceived a quieter NICU sound environment during and after sessions. Conclusion: Live-performed music therapy for extremely and very preterm infants is feasible and well tolerated, and is experienced as an added value to developmental care. Future studies should assess both short-term and long-term effects, to determine whether this intervention should be part of routine care at the NICU and whether it is most beneficial to start shortly after birth.